PENGARUH BERBAGAI JENIS PUPUK ORGANIK DAN NPK 16:16:16 TERHADAP PERTUMBUHAN SERTA PRODUKSI TANAMAN BAWANG MERAH (Allium ascalonicum L.) PADA TANAH ULTISOL - Dinda Try Agustina; Sulhaswardi (DINAMIKA PERTANIAN, 2025)
Ultisol soils are characterized by low pH and very low contents of organic matter and essential nutrients (N, P, and K), thus requiring amelioration to support shallot cultivation. This study aimed to evaluate the interaction effects and main effects of various organic fertilizers and NPK 16:16:16 fertilizer rates on the growth and yield of shallots grown on Ultimo soil. The experiment was conducted at the Experimental Farm of Universitas Islam Riau from December 2023 to March 2024 using a factorial Completely Randomized Design with three replications. The first factor was the type of organic fertilizer, consisting of kenaf leaf compost, oil palm empty fruit bunch compost (EFB/KKS), cattle manure, and poultry manure, each applied at 2 kg plot⁻¹. The second factor was the rate of NPK 16:16:16 fertilizer, namely 0, 30, 45, and 60 g plot⁻¹. Observed variables included vegetative growth, yield components, and changes in soil pH. The results showed a significant interaction between organic fertilizer type and NPK rate on all growth and yield parameters. The best treatment combination was EFB compost at 2 kg plot⁻¹ combined with NPK 16:16:16 at 60 g plot⁻¹ (P2N3). Individually, EFB compost and the 60 g plot⁻¹ NPK rate also produced the best main effects. Finally, the combined application of EFB compost and NPK 16:16:16 significantly improved soil pH, vegetative growth, and shallot yield on Ultimo soil and is recommended for shallot cultivation on similar marginal lands.